Cadmium (Cd) Content in Sediments Along the Somber River, Balikpapan City, East Kalimantan - Mufidah, Fitriatul; Paputungan, Mohammad Sumiran; Ritonga, Irwan Ramadhan (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Human activities in the Somber River area of Balikpapan, such as settlements, industry, shipping, and fisheries, have the potential to cause cadmium (Cd) contamination, threatening the mangrove ecosystem and aquatic biota. This study aimed to determine the concentration and contamination level of Cd in the sediments of the Somber River, Balikpapan. Sediment samples were systematically collected from four stations representing different anthropogenic influences, using a hand corer (50 cm depth). Cadmium concentration was analyzed using Atomic Absorption Spectrophotometry (AAS) following acid digestion. It was found that the Cd concentrations ranged from 0.04 to 1.01 µg/g, with an average of 0.37 ± 0.29 µg/g dry weight. All values were below the national sediment quality guideline. The accumulation of Cd showed an increasing trend with greater sediment depth. The calculated Contamination Factor (CF) indicated low to moderate contamination levels at all stations. Overall, the sources of Cd along the Somber River originate from both natural processes and anthropogenic activities from the land.